PUBLIC CORPORATION MANAGERS' LEADERSHIP STYLES AND MOTIVATIONS' EFFECTS ON CORPORATION EMPLOYERS' JOB SATISFACTION AND CORPORATION COMMITMEN (Third Sector Social Economic Review, 2015)
Managers’ motivation to their job with leadership characteristic has an important role to affect their subordinates’ position for the job in an organization. In our study, the public sector managers’ leadership characteristic with their job motivations to subordinates’ job satisfaction and their loyalty has been explained. In order to reach this objective, we have implemented a survey to 400 employees from 17 public sector organizations. However, 382 survey results have been chosen and considered suitable for our study. As a result, the study showed that managers’motivation and their leadership characteristic has an effect to subordinates’ job satisfaction and their organizational loyalty
Keywords: Leader; leadership characteristics; motivation; job satisfaction; public sector; organizational loyalty